Between Home and Hospital: Midwives and Their Maternity Wards in Postwar Poland (1945–1970) (Theatrum historiae, 2020)
The article’s aim is to describe the history of maternity wards, institutions that were unknown in prewar Poland. By presenting the midwives narratives in interviews this article focuses on the unique form of obstetric care on local community level, organized and managed by midwives. The article will not be a chronological description of the creation and development of maternities, but more a coverage of events that influenced their creation and activities.
Keywords: Maternity ward; Midwife in Poland; Midwifery in postwar Poland; childbirth in postwar Poland